Teamwork Competence among Health Students in the Implementation of Interprofessional Education (IPE) - Fatikhu Yatuni Asmara; Gita Rahayu Rachmawati (Holistic Nursing and Health Science, 2025)
Introduction: Interprofessional education (IPE) facilitates the development of interprofessional competencies, such as communication and teamwork. However, challenges in developing teamwork competencies can affect the enhancement of other competencies, such as communication and vision of a team. Additionally, teamwork is also affected by the previous learning process in silo professional. However, there are limited studies report the differences of teamwork among health students in different subjects. This study aims to identify the teamwork competence among health students in the IPE program.Methods: We used a descriptive research approach. We involved 470 students of semester 6th from various disciplines (medicine, nursing, and nutrition) as participants (total sampling), and a total of 431 students participated in the study (response rate: 92%). They were asked to complete the teamwork scale (TWS) online. Descriptive frequencies were used to analyze the data by identifying means and standard deviation (SD). Additionally, differences in teamwork scores among students from different subjects were analyzed by applying Kruskal-Wallis test since the data had abnormal distribution.  Result:  Nutrition students have lower scores compared to their peers in medicine and nursing in all subscales. There were differences in teamwork competencies among health students in different subjects in all subscales (team structure, leadership, situational monitoring, mutual support, and communication) with p-values 0.000; 0.000; 0.005; 0.000; 0.000, respectively. Discussion/Suggestions: The teamwork competence in all subscales was varied and it was different among students based on their subjects. It is suggested to identify students’ teamwork in other institutions and different settings, such as clinical settings, and to identify the nature of differences in achieving teamwork competence to support a deeper understanding of its achievement.